Mature cystic extragonadal teratoma in Douglas’ pouch: Case report and literature review - Yang, Yun; Zhao, Mengru; Chen, Mengyue; Tang, Huimin; Qin, Zhenyue; Liu, Junling; Wang, Huihui; Bao, Mingyue; Chen, Jiming; Xia, Bairong (Frontiers in Medicine, 2023)
Abstract: Teratomas often occur in the gonads, while Extragonadal mature cystic teratomas are reported occasionally, with the most common site being the omentum. teratoma in the Douglas sac is extremely rare. we report a rare case of mature cystic teratoma in the Douglas sac in a 71-year-old woman who underwent laparoscopic surgery. A cyst with a diameter of approximately 6 cm from Douglas was found during surgery, and the mass was separated from both ovaries. Microscopically, the cyst was a mature cystic teratoma that did not originate from the ovary.